Cement raw material with high sunlight absorptivity as well as preparation method and application of cement raw material

By mixing Ca(OH)2 with the original cement raw material and adding a mixed solution of copper nitrate and manganese nitrate to produce precipitate, it is evenly distributed on the surface of the original cement raw material, the problem of low absorption of sunlight by white cement clinker is solved, and the high absorption of sunlight by cement raw material is achieved, calcining efficiency is improved and energy consumption is reduced.

CN119797783AActive Publication Date: 2025-04-11BEIJING UNIV OF TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510074560.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-11
Estimated Expiration
2045-01-17

AI Technical Summary

Technical Problem

In the prior art, the absorption rate of white cement clinker to sunlight is very low and cannot be generated by direct irradiation, resulting in low calcination efficiency and high energy consumption when using solar energy to produce cement clinker.

Method used

By mixing Ca(OH)2 with the original cement raw material and adding a mixed solution of copper nitrate and manganese nitrate to produce a precipitate, so that it is evenly distributed on the surface of the original cement raw material, cement raw material with high sunlight absorption was prepared.

Benefits of technology

The absorption rate of cement raw materials to sunlight is greatly improved, the calcination efficiency is improved, and the energy consumption of cement production is reduced. The prepared cement clinker and cement have good mechanical properties.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of cement preparation, in particular to a cement raw material with high sunlight absorptivity and a preparation method and application thereof.The cement raw material is prepared by mixing Ca (OH) 2 and an original cement raw material, adding the mixture into a mixed solution of copper nitrate and manganous nitrate to react to generate precipitates, and enabling the precipitates to be evenly distributed on the surface of the original cement raw material; the cement raw material with the high sunlight absorptivity is prepared through the method, and the sunlight absorption of the cement raw material can be greatly improved when the cement clinker is produced through solar energy, so that the calcination efficiency is improved, and the cement production energy consumption is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of cement preparation, and in particular to a cement raw material with high sunlight absorption rate, and a preparation method and application thereof. Background Art

[0002] The energy structure of the cement industry is mainly coal-fired, accounting for about 85%, and is an energy-resource intensive industry. Carbon dioxide emissions in the cement industry mainly come from the clinker production process, accounting for about 95% of the carbon emissions of the entire cement industry. Among them, the carbonate decomposition process is the main source of carbon emissions in the cement production process, and fuel combustion is the second largest source of carbon emissions in the cement production process. Therefore, the use of an energy source that does not emit carbon dioxide can effectively reduce carbon dioxide emissions in the cement industry. Solar energy is an inexhaustible renewable energy source and one of the most widely used renewable energy sources. Therefore, relevant scholars have proposed using solar energy to provide heat for the calcination of cement clinker, and this has been put into practice.

[0003] In the process of using solar energy to produce cement clinker, sunlight directly irradiates on the cement clinker. When relevant scholars used SF40 solar furnace to produce Portland cement clinker, the chemical and mineral data of the produced gray clinker were very similar to those of standard cement. However, when producing white cement, the clinker produced was very different from the standard. This is because white cement clinker has a very low absorption rate for sunlight and therefore cannot be produced by direct irradiation. Summary of the invention

[0004] In order to solve the problems existing in the prior art, the present invention provides a cement raw material with high sunlight absorption rate, specifically, by 2 It is mixed with the original cement raw material, added into a mixed solution of copper nitrate and manganese nitrate to react and generate a precipitate, and the precipitate is evenly distributed on the surface of the original cement raw material to prepare a cement raw material with a high solar absorption rate. When using solar energy to produce cement clinker, the cement raw material can greatly increase its absorption of sunlight, thereby improving the calcination efficiency and reducing the energy consumption of cement production.

[0005] Specifically, the method for preparing cement raw material with high sunlight absorptivity of the present invention comprises the following steps: 1) Weigh the raw materials according to the ratio, 2) Put Mn(NO 3 ) 2 and Cu(NO 3 ) 2 Dissolve in water and stir evenly to obtain a mixed solution. 3) Ca(OH) 2 Add to the original cement raw material and mix evenly, then add to the mixed liquid to obtain a suspension. 4) Stir the suspension at a constant temperature. 5) Dry and grind to obtain.

[0006] The present invention is achieved by mixing Ca(OH) 2 Mixed with the original cement raw material, added to the copper nitrate and manganese nitrate mixed solution to react and generate precipitation, and evenly distributed on the surface of the original cement raw material, the precipitation gradually forms binary oxides and other substances during the cement calcination process. The present invention shows that materials with a suitable band gap can absorb the radiation of sunlight to the greatest extent, which is manifested as high absorption of incident light in a macroscopic sense. The present invention has concluded through a large number of experimental studies that Cu and Mn have an ideal band gap, and the emissivity of the materials doped with oxygen atoms in the infrared region is reduced, which can better absorb sunlight, and, in order to better achieve the clinker burning effect, the precipitate is generated on the surface of the original cement raw material through the method of the present invention. During the calcination of the cement material, as the temperature increases, copper manganese oxides are gradually formed. Compared with the addition of the same proportion of oxides, the synthesis on the surface makes its surface area larger, which can more effectively absorb sunlight, thereby improving the absorption rate of cement raw material to sunlight.

[0007] Preferably, Mn(NO 3 ) 2 and Cu(NO 3 ) 2 The molar ratio is (1.8-2.2):1, Ca(OH) 2 and Cu(NO 3 ) 2 The molar ratio is (2.8-3.2):1, Mn(NO 3 ) 2 It accounts for 0.8-4% of the original cement raw material mass.

[0008] Preferably, the original cement raw material ratio in step 3) is: KH=0.87±0.02, SM=2.56±0.02, IM=1.50±0.02. Studies have shown that, unlike traditional cement clinker burning, using sunlight to burn cement clinker requires adjusting the original cement raw material ratio to achieve a better burning effect.

[0009] Preferably, the liquid-to-solid mass ratio of the suspension in step 3) is (1-1.2):1.

[0010] Preferably, in step 2), the stirring speed is 500-600 rpm and the stirring time is 30-40 min.

[0011] Preferably, in step 4), the constant temperature is 70-80° C., the stirring speed is 900-1000 rpm, and the time is 60-90 min.

[0012] Preferably, in step 5), the drying temperature is 100-110° C., and the powder is ground to a particle size of less than 200 μm.

[0013] The present invention also relates to a cement raw material with high sunlight absorption rate, which is specifically prepared by the above-mentioned preparation method.

[0014] The present invention also relates to cement clinker, which is specifically formed by burning the above-mentioned cement raw material in a solar light concentrating device.

[0015] The present invention also relates to cement, specifically, prepared from the above-mentioned cement clinker. More preferably, the cement is ground from the above-mentioned cement clinker and gypsum. More preferably, the cement is ground from the above-mentioned cement clinker, gypsum and a mixture.

[0016] The invention also relates to the application of the cement in preparing building material products.

[0017] The present invention has the following technical advantages: 1. The present invention synthesizes copper and manganese on the surface of the original cement raw material, and gradually forms copper and manganese oxides and other substances during the calcination process to increase the cement raw material's absorption rate of sunlight, get rid of the dependence on traditional fossil energy, and has the effect of low energy consumption and clean energy. 2. The method of adding copper manganese oxide in the present invention is to directly synthesize it on the surface of the original cement raw material. When the addition amount is the same, the absorption rate of sunlight is greatly improved. 3. The cement clinker and cement prepared by the present invention have good mechanical properties and meet the use requirements. DETAILED DESCRIPTION

[0018] In order to characterize the technical effect of the present invention, cement raw meal was prepared, 5% of water was added to the raw meal and mixed evenly, the raw meal was pressed into a cake with a diameter of 50 mm and a height of 5 mm by a pressing method, and the raw meal was heated to 800°C, 950°C, 1100°C, 1250°C and 1400°C respectively by using a solar concentrating device, and quenched to room temperature after reaching the set temperature, and the absorbance of the raw meal samples at room temperature and the samples after heating and quenching was tested by using an ultraviolet-visible-near infrared spectrophotometer, the wavelength range of the test was 280-2500nm, the scanning slit length was 2nm, the scanning step length was 5nm, and the weighted absorption ratio of sunlight was calculated to complete the raw meal test, and then the cement raw meal was fired into clinker by using a solar concentrating device, and after cooling, 4% gypsum and 10% fly ash were added and ground to less than 75μm to obtain cement, and pure slurry specimens were prepared according to national standards and the mechanical properties were tested. During the test, the original cement raw material ratio values ​​were: KH=0.87, SM=2.56, IM=1.50.

[0019] Example 1, cement raw material, the preparation method comprises the following steps: 1) weighing each raw material according to the proportion, 2) mixing Mn(NO 3 ) 2 and Cu(NO 3 ) 2 Dissolve in water and stir evenly to obtain a mixed solution. 3) Add Ca(OH) 2 Add to the original cement raw material and mix evenly, then add to the mixed liquid to obtain a suspension, 4) stir the suspension under constant temperature conditions, 5) dry and grind to a particle size of less than 200 μm, and obtain, among which, Mn(NO 3 ) 2 and Cu(NO 3 ) 2 The molar ratio is 2:1, Ca(OH) 2 and Cu(NO 3 ) 2 The molar ratio is 3.1:1, Mn(NO 3 ) 2 It accounts for 0.8% of the original cement raw material mass, and the liquid-to-solid mass ratio in the suspension is 1.1:1.

[0020] After testing, the weighted absorption ratio of sunlight of cement raw material at room temperature is 33.59%, the weighted absorption ratio after sunlight treatment at 800℃ is 32.59%, the weighted absorption ratio after sunlight treatment at 950℃ is 29.55%, the weighted absorption ratio after sunlight treatment at 1100℃ is 30.97%, the weighted absorption ratio after sunlight treatment at 1250℃ is 41.31%, and the weighted absorption ratio after sunlight treatment at 1400℃ is 56.76%. The 3d compressive strength of cement slurry specimen is 23.6MPa, the 7d compressive strength is 35.8MPa, and the 28d compressive strength is 49.2MPa.

[0021] Example 2, cement raw material, the preparation method comprises the following steps: 1) weighing each raw material according to the proportion, 2) mixing Mn(NO 3 ) 2 and Cu(NO 3 ) 2 Dissolve in water and stir evenly to obtain a mixed solution. 3) Add Ca(OH) 2 Add to the original cement raw material and mix evenly, then add to the mixed liquid to obtain a suspension, 4) stir the suspension under constant temperature conditions, 5) dry and grind to a particle size of less than 200 μm, and obtain, among which, Mn(NO 3 ) 2 and Cu(NO 3 ) 2 The molar ratio is 2.1:1, Ca(OH) 2 and Cu(NO 3 ) 2 The molar ratio is 3:1, Mn(NO3 ) 2 It accounts for 3.5% of the original cement raw material mass, and the liquid-solid mass ratio in the suspension is 1.1:1.

[0022] After testing, the weighted absorption ratio of sunlight of cement raw material at room temperature is 42.12%, the weighted absorption ratio after sunlight treatment at 800℃ is 41.87%, the weighted absorption ratio after sunlight treatment at 950℃ is 32.97%, the weighted absorption ratio after sunlight treatment at 1100℃ is 36.02%, the weighted absorption ratio after sunlight treatment at 1250℃ is 47.05%, and the weighted absorption ratio after sunlight treatment at 1400℃ is 58.31%. The 3d compressive strength of cement slurry specimen is 24.9MPa, the 7d compressive strength is 37.3MPa, and the 28d compressive strength is 50.8MPa.

[0023] Comparative Example 1, cement raw material, the preparation method comprises the following steps: 1) weighing each raw material according to the proportion, 2) mixing Mn(NO 3 ) 2 Dissolve in water and stir evenly to obtain a mixed solution. 3) Add Ca(OH) 2 Add to the original cement raw material and mix evenly, then add to the mixed liquid to obtain a suspension, 4) stir the suspension under constant temperature conditions, 5) dry and grind to a particle size of less than 200 μm, and obtain, wherein, Ca(OH) 2 and Mn(NO 3 ) 2 The molar ratio is 3.1:1, Mn(NO 3 ) 2 It accounts for 0.8% of the original cement raw material mass, and the liquid-to-solid mass ratio in the suspension is 1.1:1.

[0024] After testing, the weighted absorption ratio of sunlight of cement raw material at room temperature is 27.10%, the weighted absorption ratio after sunlight treatment at 800℃ is 27.87%, the weighted absorption ratio after sunlight treatment at 950℃ is 25.56%, the weighted absorption ratio after sunlight treatment at 1100℃ is 25.21%, the weighted absorption ratio after sunlight treatment at 1250℃ is 35.16%, and the weighted absorption ratio after sunlight treatment at 1400℃ is 50.23%. The 3d compressive strength of cement slurry specimen is 19.8MPa, the 7d compressive strength is 29.7MPa, and the 28d compressive strength is 45.3MPa.

[0025] Comparative Example 2, cement raw material, the preparation method comprises the following steps: 1) weighing each raw material according to the proportion, 2) mixing Cu(NO 3 ) 2 Dissolve in water and stir evenly to obtain a mixed solution. 3) Add Ca(OH) 2Add to the original cement raw material and mix evenly, then add to the mixed liquid to obtain a suspension, 4) stir the suspension under constant temperature conditions, 5) dry and grind to a particle size of less than 200μm, to obtain, wherein, Ca(OH) 2 and Cu(NO 3 ) 2 The molar ratio is 3.1:1, Cu(NO 3 ) 2 It accounts for 0.8% of the original cement raw material mass, and the liquid-to-solid mass ratio in the suspension is 1.1:1.

[0026] After testing, the weighted absorption ratio of sunlight of cement raw material at room temperature is 24.76%, the weighted absorption ratio after sunlight treatment at 800℃ is 25.90%, the weighted absorption ratio after sunlight treatment at 950℃ is 24.62%, the weighted absorption ratio after sunlight treatment at 1100℃ is 25.38%, the weighted absorption ratio after sunlight treatment at 1250℃ is 35.44%, and the weighted absorption ratio after sunlight treatment at 1400℃ is 49.92%. The 3d compressive strength of cement slurry specimen is 19.6MPa, the 7d compressive strength is 29.3MPa, and the 28d compressive strength is 46.1MPa.

[0027] Comparative Example 3, cement raw material, the preparation method comprises the following steps: 1) weighing each raw material according to the proportion, 2) mixing Mn(NO 3 ) 2 and Cu(NO 3 ) 2 Dissolve in water and stir evenly to obtain a mixed solution; 3) Add NaOH to the original cement raw material and mix evenly, then add it to the mixed solution to obtain a suspension; 4) Stir the suspension at a constant temperature; 5) Dry and grind to a particle size of less than 200 μm to obtain, wherein Mn(NO 3 ) 2 and Cu(NO 3 ) 2 The molar ratio of NaOH and Cu(NO is 2:1. 3 ) 2 The molar ratio is 3.1:1, Mn(NO 3 ) 2 It accounts for 0.8% of the original cement raw material mass, and the liquid-to-solid mass ratio in the suspension is 1.1:1.

[0028] After testing, the weighted absorption ratio of sunlight of cement raw material at room temperature is 25.57%, the weighted absorption ratio after sunlight treatment at 800℃ is 24.28%, the weighted absorption ratio after sunlight treatment at 950℃ is 23.96%, the weighted absorption ratio after sunlight treatment at 1100℃ is 24.08%, the weighted absorption ratio after sunlight treatment at 1250℃ is 34.32%, and the weighted absorption ratio after sunlight treatment at 1400℃ is 49.81%. The 3d compressive strength of cement slurry specimen is 18.7MPa, the 7d compressive strength is 28.3MPa, and the 28d compressive strength is 43.8MPa.

[0029] Comparative Example 4, cement raw material, the preparation method comprises the following steps: 1) weighing each raw material according to the proportion, 2) mixing Ca(OH) 2 Add to the original cement raw material and mix evenly, grind to a particle size of less than 200 μm to obtain, wherein Ca(OH) 2 It accounts for 0.8% of the original cement raw material mass.

[0030] After testing, the weighted absorption ratio of sunlight of cement raw material at room temperature is 20.69%, the weighted absorption ratio after sunlight treatment at 800℃ is 22.44%, the weighted absorption ratio after sunlight treatment at 950℃ is 21.33%, the weighted absorption ratio after sunlight treatment at 1100℃ is 22.15%, the weighted absorption ratio after sunlight treatment at 1250℃ is 30.21%, and the weighted absorption ratio after sunlight treatment at 1400℃ is 42.65%. The 3d compressive strength of cement slurry specimen is 16.2MPa, the 7d compressive strength is 25.1MPa, and the 28d compressive strength is 36.3MPa.

[0031] Comparative Example 5 is different from Example 1 in that the original cement raw material ratio values ​​are: KH=0.98, SM=2.0, IM=1.36, and the others are the same.

[0032] After testing, the weighted absorption ratio of sunlight of cement raw material at room temperature is 26.49%, the weighted absorption ratio after sunlight treatment at 800℃ is 26.91%, the weighted absorption ratio after sunlight treatment at 950℃ is 25.07%, the weighted absorption ratio after sunlight treatment at 1100℃ is 24.76%, the weighted absorption ratio after sunlight treatment at 1250℃ is 35.22%, and the weighted absorption ratio after sunlight treatment at 1400℃ is 50.34%. The 3d compressive strength of cement slurry specimen is 19.4MPa, the 7d compressive strength is 28.8MPa, and the 28d compressive strength is 43.2MPa.

[0033] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing cement raw material with high sunlight absorption rate, characterized in that: The steps include: 1) Weigh the raw materials according to the ratio, 2) Dissolve Mn(NO3)2 and Cu(NO3)2 in water and stir evenly to obtain a mixed solution, wherein the molar ratio of Mn(NO3)2 to Cu(NO3)2 is (1.8-2.2):1, the molar ratio of Ca(OH)2 to Cu(NO3)2 is (2.8-3.2):1, and Mn(NO3)2 accounts for 0.8-4% of the original cement raw material mass; 3) Add Ca(OH)2 to the original cement raw material and mix evenly, then add it to the mixed solution to obtain a suspension. The original cement raw material ratio values ​​are: KH=0.87±0.02, SM=2.56±0.02, IM=1.50±0.02; 4) Stir the suspension at a constant temperature. 5) Dry and grind to obtain.

2. The preparation method according to claim 1, characterized in that: The liquid-to-solid mass ratio of the suspension in step 3) is (1-1.2):

1.

3. The preparation method according to claim 1, characterized in that: In step 2), the stirring speed is 500-600 rpm and the stirring time is 30-40 min.

4. The preparation method according to claim 1, characterized in that: In step 4), the constant temperature is 70-80°C.

5. The preparation method according to claim 1, characterized in that: In step 5), the drying temperature is 100-110°C and the powder is ground to a particle size of less than 200 μm.

6. A cement raw material with high sunlight absorption rate, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 5.

7. Cement clinker, characterized in that The cement raw material according to claim 6 is fired in a solar light concentrating device.

8. Cement, characterized in that Prepared from the cement clinker described in claim 7.

Citation Information

Patent Citations

  • Radiative insulating water-based coating and preparation method thereof

    CN104277641A

  • Efficient solar floor tile

    CN106192655A

  • Method and system for calcining cement clinker through microwaves and electric energy

    CN114249551A

  • Raw materials combustion adjuvant

    CN1837122A

  • Improvements in and connected with the manufacture of cement

    GB320597A